RESIDU PESTISIDA DIAZINON DALAM SAYURAN KUBIS (Brassica olarecea) - Azis, Thamrin; Wahyuni, Sri; Muzakkar, Muhammad Zakir (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2020)
ABSTRACTThe presence of pesticide residues in vegetables is a food safety problem. This research aimed to analyze the performance of biosensor made of platinum (Pt) coated with active ingredient butyrylcholinesterase enzymes in detecting diazinon residues in cabbages. This research used supporting materials of cellulose acetate (SA) and glutaraldehyde (GA) in various compositions. This study evaluated the absorption (potential) of each electrode composition to the time of the last spraying of the diazinon residue in cabbages. Diazinon residual levels were measured in cabbages at the last spraying time interval (0 days, 5 days, 10 days, 15 days) of each electrode composition.The results of absorption measurements (potential) of each electrode against time intervals (0 days, 5 days, 10 days, 15 days) show that the lowest levels of diazinon residue were found in samples on electrodes SA 5.0% GA (10%, 15%, and 20% ) with the last spraying interval of 0 days before harvest of 0.390 ppm, 1,620 ppm, and 0.026 ppm, respectively. Meanwhile, the highest residue was found in cabbage samples with the last spraying interval of 5 days before harvest, which were 28.80 ppm, 27.0 ppm, and 17.0 ppm. The results show that the designed biosensors can detect diazinon residues in cabbages.Keywords: Pesticide, Biosensor, potentiometric, enzyme buirilcholinesteraseABSTRAKKeberadaan residu pestisida dalam sayuran merupakan masalah keamanan pangan. Penelitian ini bertujuan menganalisis hasil aplikasi desain biosensor terbuat dari kawat platina (Pt) terlapis bahan aktif enzim butirilkolinesterase dalam mendeteksi residu diazinon pada sayuran kubis. Penelitian ini menggunakan bahan pendukung membran selulosa asetat (SA) dan glutaldehid (GA) berbagai komposisi. Penelitian ini mengevaluasi serapan (potensial) dari masing-masing komposisi elektroda biosensor terhadap waktu penyeprotan terakhir residu diazinon pada sayuran kubis. Kadar residu diazinon diukur dalam sayuran kubis dengan interval waktu penyemprotan terakhir (0 hari, 5 hari,10 hari, 15 hari) dari masing-masing komposisi elektroda.Hasil pengukuran serapan (potensial) setiap elektroda biosensor terhadap interval waktu (0 hari, 5 hari, 10 hari, 15 hari) adalah kadar residu diazinon terendah terdapat sampel sayuran kubis pada elektroda SA 5,0 % GA (10 % , 15 % dan 20 %) dengan interval waktu penyemprotan terakhir 0 hari sebelum panen sebesar 0,390 ppm, 1,620 ppm, dan 0,026 ppm. Sementara nilai kadar residu tertinggi terdapat pada sampel kubis dengan interval waktu penyemprotan terakhir 5 hari sebelum panen yaitu sebesar 28,80 ppm, 27,0 ppm dan 17,0 ppm. Hasil penelitian membuktikan biosensor yang didesain mampu mendeteksi residu diazinon pada sayuran kubis.Kata Kunci: Pestisida, Biosensor, Potensiometri, enzim Butirilklonesterase.